Metaphors in Lyudmila Ulitskaya’s Short Story ”The Queen of Spades” - Molnár, Angelika (Slavica, 2020)
In this paper it opens up how Lyudmila Ulitskaya in her short story “The Queen of Spades”develops the crisis situation whichher heroes getsinto. So, the problems of the crisis should beanalysed also from a broader perspective, however, we will confine ourselves to only one rather narrow aspect of the analysis of poetic utterance, namely the tropological one.The chosen (mechanical and animalistic) metaphors are connected with the figure of the main heroine and also her revolting daughter.